2019
DOI: 10.1103/physreva.99.022322
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance continuous-variable measurement-device-independent quantum key distribution with discrete modulation

Abstract: We propose a long-distance continuous-variable measurement-device-independent quantum key distribution (CV-MDI-QKD) protocol with discrete modulation. This kind of discrete-modulated schemes have good compatibility with efficient error correction code, which lead to higher reconciliation efficiency even at low signalto-noise ratio (SNR). Security analysis shows that the proposed protocol is secure against arbitrary collective attacks in the asymptotic limit with proper use of decoy states. And with the using o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Studies have shown that discrete modulation is more suitable for long-distance communication than Gaussian modulation because of the relatively large key generation rate even at a lower SNR [12,31]. Up to now, different types of discretely modulated CV-QKD schemes have been investigated, including the four-state protocol, eight-state protocol, sixteen-state protocol, and so on.…”
Section: Description Of the Discrete-modulated Underwater Cv-qkdmentioning
confidence: 99%
“…Studies have shown that discrete modulation is more suitable for long-distance communication than Gaussian modulation because of the relatively large key generation rate even at a lower SNR [12,31]. Up to now, different types of discretely modulated CV-QKD schemes have been investigated, including the four-state protocol, eight-state protocol, sixteen-state protocol, and so on.…”
Section: Description Of the Discrete-modulated Underwater Cv-qkdmentioning
confidence: 99%
“…Unfortunately, developing a protocol that allows exploitation of the practicality of the CV MDI regime at long distance is a difficult problem in recent QKD theory [36][37][38][39]. A great deal of effort has been directed at improving the performance of this type of protocol, with proposals based on virtual photon subtraction [40,41], unidimensional modulation [42], or discrete modulation [43]. While these protocols offered an improvement in the range of the asymmetric configuration, in which the relay is positioned within close range of one of the parties, their applicability in the symmetric configuration, in which the relay is positioned equidistance between the parties, was very limited.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these practical security loopholes of CV-QKD protocols various measurement device-independent (MDI) CV-QKD protocols have been advocated [25]- [29]. The MDI QKD concept was first introduced in DV-QKD context to solve for various detector side-channel attacks [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…While the employment of MDI concept can solve for detector side-channel attacks and simultaneously extend the transmission distance for DV-QKD, this is not the case for CV-QKD applications. The achievable transmission distances for symmetric MDI-based CV-QKD schemes, wherein Charlie is located in the middle of the link (at equal distances from Alice and Bob), is extremely short [28], [29]. To extend the transmission distance of symmetric MDI CV-QKD, the extreme asymmetric case has been introduced (see for example [28], [29]); however, the transmission distances are still shorter than that of conventional CV-QKD schemes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation